Pre-clinical Imaging of Invasive Candidiasis Using ImmunoPET/MR - Morad, Hassan O. J.; Wild, Anna-Maria; Wiehr, Stefan; Davies, Genna; Maurer, Andreas; Pichler, Bernd J.; Thornton, Christopher R. (Frontiers in Microbiology, 2018)
The human commensal yeast Candida is the 4th most common cause of hospital-acquired bloodstream infections, with C. albicans accounting for the majority of the >400,000 life-threatening infections annually. Diagnosis of invasive candidiasis (IC), a disease encompassing candidemia (blood-borne yeast infection) and deep-seated organ infections, is a major challenge since clinical manifestations of the disease are indistinguishable from viral, bacterial and other fungal diseases, and diagnostic tests for biomarkers in the bloodstream such as PCR, ELISA and pan-fungal β-D-glucan lack either standardisation, sensitivity or specificity. Blood culture remains the gold standard for diagnosis, but test sensitivity is poor and turn-around time slow. Furthermore, cultures can only be obtained when the yeast resides in the bloodstream, with samples recovered from hematogenous infections often yielding negative results. Consequently, there is a pressing need for a diagnostic test that allows the identification of metastatic foci in deep-seated Candida infections, without the need for invasive biopsy. Here, we report the development of a highly specific mouse IgG3 monoclonal antibody (MC3) that binds to a putative β-1,2-mannan epitope present in high molecular weight mannoproteins and phospholipomannans on the surface of yeast and hyphal morphotypes of C. albicans, and its use as a [64Cu]NODAGA-labeled tracer for whole-body pre-clinical imaging of deep-seated C. albicans infections using antibody-guided positron emission tomography and magnetic resonance imaging (immunoPET/MRI). When used in a mouse intravenous (i.v.) challenge model that faithfully mimics disseminated C. albicans infections in humans, the [64Cu]NODAGA-MC3 tracer accurately detects infections of the kidney, the principal site of blood-borne candidiasis in this model. Using a strain of the emerging human pathogen Candida auris that reacts with MC3 in vitro, but which is non-infective in i.v. challenged mice, we demonstrate the accuracy of the tracer in diagnosing invasive infections in vivo. This pre-clinical study demonstrates the principle of using antibody-guided molecular imaging for detection of deep organ infections in IC, without the need for invasive tissue biopsy.